2014
DOI: 10.1128/jcm.02316-14
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR for Detection of Seven Virulence Factors and K1/K2 Capsular Serotypes of Klebsiella pneumoniae

Abstract: A single multiplex PCR assay targeting seven virulence factors and the wzi gene specific for the K1 and K2 capsular serotypes of Klebsiella pneumoniae was developed and tested on 65 clinical isolates, which included 45 isolates responsible for communityacquired severe human infections. The assay is useful for the surveillance of emerging highly virulent strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
139
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(147 citation statements)
references
References 28 publications
2
139
1
5
Order By: Relevance
“…Several multiplex PCR targeting virulence factors and capsular serotypes have been previously described to help characterize hvKP isolates [Bialek-Davenet et al, 2014;Compain et al, 2014;Turton et al, 2010]. Compared to regular singleplex PCR assays, we found that multiplex PCR is consistent and much quicker in detecting virulent genes and capsular types.…”
Section: Discussionmentioning
confidence: 75%
“…Several multiplex PCR targeting virulence factors and capsular serotypes have been previously described to help characterize hvKP isolates [Bialek-Davenet et al, 2014;Compain et al, 2014;Turton et al, 2010]. Compared to regular singleplex PCR assays, we found that multiplex PCR is consistent and much quicker in detecting virulent genes and capsular types.…”
Section: Discussionmentioning
confidence: 75%
“…HV K. pneumoniae likely utilizes this operon for virulence in vivo, as deletion of allS, an activator of the operon involved in this process, resulted in an HV K. pneumoniae strain with significantly reduced virulence based on the 50% lethal dose (LD 50 ) in an intragastric model of infection (361). Along these lines, the presence of this allantoin operon is enriched in strains associated with liver abscess versus commensal strains (224,362). For example, one study found that allS was present in 100% of HV K. pneumoniae isolates from Taiwan but in 0% of K2 isolates and non-K1/K2 isolates from patient blood or liver samples (227), and another study found an association between the presence of allS and the invasiveness of primary liver abscess strains (199).…”
Section: Allantoin Metabolismmentioning
confidence: 84%
“…We conducted cps genotyping of K serotype-specific alleles for K1, K2, K5, K20, K54, and K57 by PCR as previously described (19). Virulence-associated factors, such as the exopolysaccharide synthesis regulator gene (rmpA) and an iron uptake system (aerobactin), were determined by PCR (20,21). Previously reported primers used for PCR were the following: aerobactin forward, 5=-GCATAGGCGGATACGAACAT-3=; aerobactin reverse, 5=-CACAGGGCAATTGCTTACCT-3= (21).…”
mentioning
confidence: 99%